Environmental data visualisation for non-scientific contexts: Literature review and design framework. (November 2016) - Grainger, Sam; Mao, Feng; Buytaert, Wouter
Abstract: Environmental science is an applied discipline, which therefore requires interacting with actors outside of the scientific community. Visualisations are increasingly seen as powerful tools to engage users with unfamiliar and complex subject matter. Despite recent research advances, scientists are yet to fully harness the potential of visualisation when interacting with non-scientists. To address this issue, we review the main principles of visualisation, discuss specific graphical challenges for environmental science and highlight some best practice from non-professional contexts. We provide a design framework to enhance the communication and application of scientific information within professional contexts. These guidelines can help scientists incorporate effective visualisations within improved dissemination and knowledge exchange platforms. We conclude that the uptake of science within environmental decision-making requires a highly iterative and collaborative design approach towards the development of tailored visualisations. This enables users to not only generate actionable understanding but also explore information on their own terms. Highlights: Effective visualisations can engage non-scientists with unfamiliar and complex subject matter. We review the main principles of visualisation and specific graphical challenges for environmental science. We provide a design framework to help scientists develop effective visualisations within nonscientific, professional contexts. The uptake of science within environmental decision-making requires a highly iterative and collaborative design approach.